Struktury szeregów czasowych ubezpieczeń majątkowych - Melich-Iwanek, Krystyna (The structures of time series of the property insurance, 2006)
The aim of the article is to investigate the structure of time series representing insurances contracted by the chosen insurance consulting company. The distinction between life and properly insurances is especially important. The analysis embraces problems of non-stationarity and seasonality of these processes, but the most important is the location or the turning points. It has a special meaning in the context of the disastrous flood, which took place in Poland in 1997. The analysis should answer whether such event affected the quantity of insurance contracts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 78-88